Layer-by-Layer Cell Encapsulation for Drug Delivery: The History, Technique Basis, and Applications - Wenyan Li; Xuejiao Lei; Hua Feng; Bingyun Li; Jiming Kong; Malcolm Xing (MDPI AG, 2022)
The encapsulation of cells with various polyelectrolytes through layer-by-layer (LbL) has become a popular strategy in cellular function engineering. The technique sprang up in 1990s and obtained tremendous advances in multi-functionalized encapsulation of cells in recent years. This review comprehensively summarized the basis and applications in drug delivery by means of LbL cell encapsulation. To begin with, the concept and brief history of LbL and LbL cell encapsulation were introduced. Next, diverse types of materials, including naturally extracted and chemically synthesized, were exhibited, followed by a complicated basis of LbL assembly, such as interactions within multilayers, charge distribution, and films morphology. Furthermore, the review focused on the protective effects against adverse factors, and bioactive payloads incorporation could be realized via LbL cell encapsulation. Additionally, the payload delivery from cell encapsulation system could be adjusted by environment, redox, biological processes, and functional linkers to release payloads in controlled manners. In short, drug delivery via LbL cell encapsulation, which takes advantage of both cell grafts and drug activities, will be of great importance in basic research of cell science and biotherapy for various diseases.